Exploring Level of Effectivity on Public Transportation as One of Transportation Demand Management Strategy - Budiprasetya, Bagaskara; Farghani, Azmi Nofal (Department of Urban and Regional Planning, Universitas Diponegoro, 2024)
Existing road and traffic management infrastructure could not substantially accommodate the sudden surge in vehicle ownership and traffic congestion. Additionally, congestion in developing nation is additionally linked to restricted road infrastructure and a shortage of resources for traffic management. To solve the problems, experts and literature proposed Transportation Demand Management as a strategy that one of the objectives is to establish effective public transportation system. In this research, we aim to explore the effectiveness of Trans Metro Pasundan performance as one of TDM implementation in Bandung, Indonesia by examining operational measurements, such as: fleet number, vehicle utilization, load factor, accident rates; and financial measurements, such as: revenue per kilometre and cost per kilometre. As a result, Dipatiukur - Jatinangor via Toll route operates with the highest number of vehicles, Kota Baru Parahyangan - Alun-Alun Kota Bandung and Baleendah - BEC routes exhibit strong load factors, Leuwi Panjang - Soreang route's strong revenue performance. Hence, the transportation service provider should continue to focus on understanding route-specific demands, improving cost management, and maintaining high safety standards to enhance the network's overall performance and profitability.